THE ROLE OF THE PROTOCOL OFFICER OF THE ADMINISTRATIVE BUREAU OF THE REGIONAL SECRETARIAT OF NORTH SUMATRA PROVINCE IN THE SUCCESS OF THE NORTH SUMATRA GOVERNOR'S WORKING VISIT TO THE NATURAL DISASTER AREA IN PADANG TUALANG VILLAGE, PADANG TUALANG DISTRICT, LANGKAT REGENCY - Rafiq Ray; Adam; Heri Kusmanto (SOSIOEDUKASI, 2026)
This study aims to analyze the role of protocol officers of the North Sumatra Provincial Regional Secretariat Administration Bureau in the success of the North Sumatra Governor's working visit to natural disaster areas in Padang Tualang Village, Padang Tualang District, Lalat Regency, as well as identify supporting and inhibiting factors for its implementation. The research uses a qualitative approach with a single case study design. Data was obtained through in-depth interviews, field observations, and documentation, then analyzed descriptively to understand the dynamics of planning, coordination, and agenda adjustment in emergency situations. The results show that the role of protocols is not only administrative, but also strategic and adaptive, including planning functions, cross-agency coordination, communication mediation, and field observation which leads to the addition of visit locations. This success was supported by effective communication, flexibility, and leadership support, although constrained by limited resources and coordination.